The perils of gender beliefs for men leaders as change agents for gender equality - Humbert, Anne Laure; Kelan, Elisabeth; van den Brink, Marieke (Wiley, 2019)
This article examines the potentially damaging role that gender beliefs can play in hindering women's equal representation in leadership positions. Based on a secondary analysis of a large‐scale EU‐wide survey (Eurobarometer 76.1), the article shows that essentialist gender beliefs lower support for equality interventions such as quotas or targets, particularly among men as leaders. The results show that discriminatory gender beliefs partially mediate this relationship and produce a more negative effect among men leaders. The paper contributes to understanding the role essentialist gender beliefs often lay the groundwork for gender discriminatory beliefs. Those in turn hinder support for effective gender equality measures. Gender essentialist beliefs can be held by everyone but are more prevalent among men leaders. We conclude that greater gender balance in leadership cannot be achieved without tackling underlying gender beliefs, particularly among men leaders since they are called upon to enact change. We thereby argue that simply asking for men to become change agents for gender equality is not an effective strategy if underlying gender beliefs are left unchallenged.
Keywords: gender; leadership; quotas; essentialism; men; targets; beliefs